Prevalence of anemia in pregnancy: a survey from gynecological clinics in Khyber Pakhtunkhwa Pakistan - Heema; Shams, Nabila; Saleem, Maria; Rahman, Faiza; Shinwari, Kausar Rehman (International Journal of Pathology, 2025)
Background: This study aims to find the prevalence of anemia in pregnancy in district Kohat from three gynecological clinics. Methods: This cross-sectional study was conducted from August 2024 to March 2025 at gynecological clinics of Kohat including Health Ways hospital, Liaqat Memorial hospital and Dr. Jamila Rehman gyne clinic Hangu. Total 600 pregnant women via convenient sampling were enrolled in the study prior proper consent. Demographic data were recorded on pre-designed proforma and 5cc blood was withdrawn for hemoglobin (HB) analysis. All the data were entered in SPSS. Descriptive statistics were applied to represent demographics of the participants. Chi-square test was applied to find the possible association between age, education status, pregnancy and iron supplementation with the development of anemia. P-value <0.05 was border line for significance. Results: In our study the prevalence of anemia was 68% (Hb=<11gm/dl), in which 45% had mild anemia while 23% had moderate anemia and none of the women were presented with severe anemia. The mean age of 26 ± 3.5 years in which 210 (35%) were below 25 years and 390 (65%) were above 25 years of age. About 80% (480) participants were illiterate and rest had only primary education. High percentage of participants 500 (83.3%) were house wives. Majority of the participants 390 (65%) were having their first pregnancy and 420 (70%) were in their 3rd trimester. Furthermore, 252 (42%) women were having a history of taking supplements to improve anemia while rest were unaware. Increasing age, illiteracy, first pregnancy and no iron supplementation were significantly associated with the development of anemia in pregnant women with p-value <0.001 Conclusion: There is high prevalence of anemia particularly in aged women, having first pregnancy, women with low education status, low socioeconomic status and women who does not take iron rich food or iron supplementations